2016
DOI: 10.1016/j.ebiom.2016.02.043
|View full text |Cite
|
Sign up to set email alerts
|

A Selective Small Molecule DNA2 Inhibitor for Sensitization of Human Cancer Cells to Chemotherapy

Abstract: Cancer cells frequently up-regulate DNA replication and repair proteins such as the multifunctional DNA2 nuclease/helicase, counteracting DNA damage due to replication stress and promoting survival. Therefore, we hypothesized that blocking both DNA replication and repair by inhibiting the bifunctional DNA2 could be a potent strategy to sensitize cancer cells to stresses from radiation or chemotherapeutic agents. We show that homozygous deletion of DNA2 sensitizes cells to ionizing radiation and camptothecin (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
86
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 82 publications
(93 citation statements)
references
References 81 publications
7
86
0
Order By: Relevance
“…We also designed additional DNA structures ( Fig EV3), which contained one, two, or three stem/loop structures, and comprehensively mapped the cleavage sites based on the product sizes shown in the gel images. Our cleavage site mapping indicated that DNA2 nuclease activity only works on the ssDNA regions and requires its helicase activity, which is similar as previous demonstrations (Lin et al, 2013;Ronchi et al, 2013;Liu et al, 2016). This result supports the following model for resolution of multiple stem-loop structures during centromeric DNA replication: The DNA2 helicase activity first separates the stem to make a single ssDNA that is long enough (~10 nts) for nuclease cleavage; then, when the ssDNA at the junction is exposed, DNA2 cleaves the whole hairpin structure and removes the structured DNA at the replication fork.…”
Section: Concerted Action Of the Nuclease And Helicase Activities Of supporting
confidence: 92%
“…We also designed additional DNA structures ( Fig EV3), which contained one, two, or three stem/loop structures, and comprehensively mapped the cleavage sites based on the product sizes shown in the gel images. Our cleavage site mapping indicated that DNA2 nuclease activity only works on the ssDNA regions and requires its helicase activity, which is similar as previous demonstrations (Lin et al, 2013;Ronchi et al, 2013;Liu et al, 2016). This result supports the following model for resolution of multiple stem-loop structures during centromeric DNA replication: The DNA2 helicase activity first separates the stem to make a single ssDNA that is long enough (~10 nts) for nuclease cleavage; then, when the ssDNA at the junction is exposed, DNA2 cleaves the whole hairpin structure and removes the structured DNA at the replication fork.…”
Section: Concerted Action Of the Nuclease And Helicase Activities Of supporting
confidence: 92%
“…Mirin was obtained from Sigma, PFM39 and WRN inhibitors were generous gifts from J. Tainer and R. Brosh respectively. DNA2 inhibitor has been described 40 . Cisplatin and Hydroxyurea were obtained from Sigma.…”
Section: Methodsmentioning
confidence: 99%
“…Paradoxically, expression of mutp53-R273H in DNA2-depleted H1299 cells made cells become more sensitive to cisplatin, supporting the concept of a synthetic lethality approach. To further investigate the effect of mutp53 on the sensitivity to DNA2 inhibition, we expressed mutp53 in H1299 cells and then treated the cells with DNA2 small-molecule inhibitor C36 (NSC360177) or C5 (NSC15765) (40). Indeed, expression of mutp53-R273H or -R175H enhanced the sensitivity to DNA2 inhibitors (Fig.…”
Section: Mutp53 Expression and Dna2 Depletion/inhibition Together Sevmentioning
confidence: 99%